2007
DOI: 10.2106/jbjs.f.01139
|View full text |Cite
|
Sign up to set email alerts
|

Hallux Valgus and First Ray Mobility

Abstract: A proximal crescentic osteotomy of the first metatarsal combined with distal soft-tissue realignment should be considered in the surgical management of moderate and severe subluxated hallux valgus deformities. First ray mobility was routinely reduced to a normal level without the need for an arthrodesis of the metatarsocuneiform joint. Plantar gapping is not a reliable radiographic indication of hypermobility of the first ray in the sagittal plane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
126
4
15

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(149 citation statements)
references
References 39 publications
4
126
4
15
Order By: Relevance
“…While cosmesis should not be regarded as an operative indication, improvement following surgery has been associated with high patient satisfaction and should be regarded as a desirable outcome [9,13,14] . We found that the majority of our patients were able to return to these comfortable shoes without residual discomfort, demonstrating satisfactory functional outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While cosmesis should not be regarded as an operative indication, improvement following surgery has been associated with high patient satisfaction and should be regarded as a desirable outcome [9,13,14] . We found that the majority of our patients were able to return to these comfortable shoes without residual discomfort, demonstrating satisfactory functional outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Patients reporting significant pain or functional impairment unresponsive to conservative methods (footwear modification, orthotics and nonsteroidal anti-inflammatories) should be considered for joint-preserving surgical intervention (e.g., scarf ± akin osteotomy) [6][7][8][9][10] . The safety and efficacy of these procedures in the treatment of hallux valgus deformity is well described [6,[8][9][10][11][12][13] . The return to comfortable footwear (e.g., trainers, flats, boots) is a fundamental aspect of post-operative rehabilitation and is closely related to overall patient satisfaction [8,11,[14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…The foot is examined for a pes planus deformity and for contracture of the Achilles tendon, both of which may affect the choice and success of the operation. The metatarsocuneiform joint should be checked for hypermobility, mobility of more than 9 mm represents hypermobility [25], but the absolute amount of motion that constitutes hypermobility is controversial [26,27]. An interview with the patient is important not only to evaluate the major symptoms associated with the hallux valgus deformity but also to educate the patient with regard to the problem, the alternatives for treatment, and the risks and complications when an operation is indicated [2,16].…”
Section: Current Concepts For Primary Operative Treatmentmentioning
confidence: 99%
“…This procedure has been indicated for the correction of metatarsus primus varus in patients with moderate to severe hallux valgus and hypermobility of the first ray [39]. First ray hypermobility has been recommended to this procedure, but it is controversial [26]. Early reports identified nonunion rates of 10-12% with the modified Lapidus procedure.…”
Section: Current Concepts For Primary Operative Treatmentmentioning
confidence: 99%
See 1 more Smart Citation